(untitled) (Tribhuvan University Journal of Food Science and Technology, 2024)
Cacti (family Cactaceae) are drought-tolerant succulents of significant ecological, nutritional, and medicinal value, widely distributed from Canada to Patagonia and cultivated globally, particularly Opuntia ficus-indica. Their adaptive features, specialized water-storing tissues, reduced leaves, and protective spines enable survival in extreme environments and support their expanding role in agriculture. Phytochemical investigations reveal substantial quantities of alkaloids, flavonoids, saponins, polysaccharides, and phenolic compounds. Quantitative studies report phenolic contents of 120–450 mg GAE/100 g, flavonoids of 30–80 mg/100 g, saponins of 0.5–2.5%, and polysaccharides comprising 10–17% of the dry biomass. These compounds contribute to documented antioxidants, anti-inflammatory, antimicrobial, and antihyperglycemic activities. Nutritionally, edible cacti such as O. ficus-indica provide 3–7% dietary fiber, 12–17 mg of vitamin C per 100 g, and high levels of calcium and magnesium, supporting metabolic and gastrointestinal health. Their fruits and cladodes are incorporated into diverse food products, including juices, jams, fermented beverages, and functional food formulations. Cactus cultivation further supports livestock feed production, soil conservation, and sustainable agriculture in semi-arid regions where conventional crops fail. Recent evidence highlights the therapeutic potential of cactus-derived bioactive compounds in managing chronic metabolic disorders, modulating lipid and glucose profiles, and reducing oxidative stress. Increasing global demand for sustainable, climate-resilient crops and natural functional ingredients underscores the growing relevance of cacti. Overall, the integration of phytochemical richness, nutritional value, and environmental resilience positions cacti as promising resources for future nutraceutical, pharmaceutical, and food industry applications.